STRATEGI PENGEMBANGAN USAHA PETERNAKAN AYAM KAMPUNG KABUPATEN JEMBER - Wiranata, Muhammad Ardi (Jurnal Sains Agribisnis, 2024)
Aim from research this is identify and analysis internal factor environment – ekstermal influences business, recommendation alternative strategy in order development business and determine scale priority strategy development business farm local Chicken. Research this held start month July-September 2023 is farm local chicken in jember selected in a manner purposive sampling with see data form all aspect of the internal as well as external company. Concluded research internal factors that become the main strength possessed by the company is having their own market / market partners, while the one that makes weakness is the availability of Low DOC. External factors that become the main opportunity are the lack of competitors, while the main threat is there are similar chickens, namely super chicken. The position of Local Chicken Farming Kabupaten Jember company is in cell V, and at this position can be managed through a strategy of keep and maintaining (Hold and maintain) with a choice of market penetration and product development strategies. Priority scale strategies include strategy 3 adding brood populations and improving hatching machines